Exploring the influence of oral and gut microbiota on ulcerative mucositis: a pilot cohort study - Bartha, Valentin; Boutin, Sébastien; Schüßler, Dorothée L.; Felten, Anna; Fazeli, Shila Marlen; Kosely, Florentina; Luft, Thomas; Wolff, Diana; Frese, Cornelia; Schoilew, Kyrill (Oral diseases, 2025)
Aim Comparing oral and gut microbiome profiles between patients with and without ulcerative mucositis during allogeneic stem cell transplantation (aSCT). Materials and Methods Specimens from oral mucosa, saliva, and stool were collected pre-(T0) and post- (T0 +28d ± 14d) aSCT (T1). Microbiome structure differences were analyzed by 16S-rRNA-gene sequencing, and associations to patients' clinical characteristics were investigated. Results Ten of 25 included patients developed ulcerations. The α-diversity decreased between T0 and T1, independent of ulcerations. PERMANOVA revealed differences in beta diversity between T1 stool samples from patients with and without ulcerations. At T1, saliva samples of patients with ulcerations showed an increase of Mycoplasma salvarius, while commensals decreased in saliva and mucosal swabs. The gut microbiome of both groups showed an overabundance of Enterococcus spp., associated with inflammatory conditions. Salival α-diversity of older and overweight patients decreased slower, whereas in mucosal swabs mucositis or impaired renal function was associated with a higher decline. Female gender and history of periodontitis were associated with increased stool microbiome changes, while self-reported probiotics intake was related to reduced changes. Conclusions Ulcerations appeared in 40% of the patients. Distinct microbial changes, including increased abundance of Mycoplasma salivarius in saliva and decreased abundance of commensals, marked those with ulcerations. Trial Registration The study was registered in the German Register for Clinical Studies (DRKS00032882)
Gesehen am 06.11.2025